"You Can't Just Walk Down the Street and Meet Someone": The Intersection of Social–Sexual Networking Technology, Stigma, and Health Among Gay and Bisexual Men in the Small City. (May 2017) - White Hughto, Jaclyn M.; Pachankis, John E.; Eldahan, Adam I.; Keene, Danya E.
Social–sexual networking technologies have been reported to yield both psychosocial benefits and sexual risks for gay and bisexual men, yet little research has explored how technology interacts with the social–geographical environment to shape the health of gay and bisexual men in the relatively understudied environment of small cities. This article draws on 29 semistructured interviews examining the use of social–sexual networking technologies among racially diverse gay and bisexual men in two small cities. Questions probed participants' use of technology to meet sexual partners, engagement in the gay community, and the role of virtual and nonvirtual spaces in relation to health. Findings suggest that social networking technologies can help men navigate the challenges of small cities, including small and insular gay communities, lack of dedicated gay spaces, and sexual minority stigma. However, participants also describe declines in gay community visibility and cohesion, which they attribute to technology use. The article concludes by discussing the intersections of virtual and physical space in small cities as sites for the production of health and illness.